2020
DOI: 10.3892/etm.2020.8691
|View full text |Cite
|
Sign up to set email alerts
|

N,N‑diethylaminobenzaldehyde targets aldehyde dehydrogenase to eradicate human pancreatic cancer cells

Abstract: Pancreatic cancer is a common cause of worldwide cancer-related mortality with a poor 5-year survival rate. Aldehyde dehydrogenase (ALDH) activity is a possible marker for malignant stem cells in solid organ systems, including the pancreas, and N,N-diethylaminobenzaldehyde (DEAB) is able to inhibit ALDH activity. In the present study, the role of DEAB in the treatment of pancreatic cancer cells and the potential underlying mechanisms were investigated. The ALDH activities of pancreatic cancer cell lines treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Furthermore, endometrial spheres obtained under DEAB influence during the five-day sphere-formation protocol exhibited a significant decrease in the projection area (Figure 2b), suggesting a potential impact on CSC proliferation. Similar effects of DEAB on the proliferation and colony-forming capacity were observed in pancreatic cells [44].…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, endometrial spheres obtained under DEAB influence during the five-day sphere-formation protocol exhibited a significant decrease in the projection area (Figure 2b), suggesting a potential impact on CSC proliferation. Similar effects of DEAB on the proliferation and colony-forming capacity were observed in pancreatic cells [44].…”
Section: Discussionsupporting
confidence: 72%
“…ALDH1 is a cancer stem cell marker in some tumors [ 28 , 29 ], including pancreatic adenocarcinoma [ 30 , 31 ]. We assessed ALDH1 activity after DCA treatment in Capan-2 cells using the aldefluor assay.…”
Section: Resultsmentioning
confidence: 99%
“…Identification of CSCs is frequently carried out using the Aldefluor assay, which includes the addition of 4-(diethylamino)­benzaldehyde (DEAB), a small-molecule inhibitor that is used as a control to identify subpopulations of cells with high ALDH expression (ALDH high ) and with SC-like properties . DEAB is a pan-ALDH inhibitor, which has been found to delay differentiation of CSCs, , also showing potential in combination treatments with other drugs. Early work showed that 4-(dipropylamino)­benzaldehyde was more potent than DEAB as a reversible inhibitor against mouse and human ALDH1, with variable inhibitory effects according to the selected substrate . In the same study, 4-(dimethylamino)­benzaldehyde and 4-(dibutylamino)­benzaldehyde showed low binding affinity to ALDH1 but provided no information on isoform selectivity .…”
Section: Introductionmentioning
confidence: 99%